2013
DOI: 10.1053/j.gastro.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

IDO1 Metabolites Activate β-catenin Signaling to Promote Cancer Cell Proliferation and Colon Tumorigenesis in Mice

Abstract: BACKGROUND & AIMS Indoleamine 2,3 dioxygenase-1 (IDO1) catabolizes tryptophan along the kynurenine pathway. Though IDO1 is expressed in inflamed and neoplastic epithelial cells of the colon, its role in colon tumorigenesis is not well understood. We used genetic and pharmacologic approaches to manipulate IDO1 activity in mice with colitis-associated cancer and human colon cancer cell lines. METHODS C57Bl6 wild type (control), IDO1−/−, Rag1−/−, Rag1/IDO1 double knockout mice were exposed to azoxymethane and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(185 citation statements)
references
References 40 publications
9
164
4
Order By: Relevance
“…IDO is produced not only by some tumors but also by inhibitory immune cells such as suppressive dendritic cells and monocyte-derived macrophages (27,28). In fact, IDO expression within the tumor microenvironment and tumor draining lymph nodes correlates with poor cancer prognosis (29)(30)(31)(32). IDO enzymatic activity potentiates tryptophan degradation, causing cell-cycle arrest and induction of anergy in effector T cells.…”
Section: Introductionmentioning
confidence: 99%
“…IDO is produced not only by some tumors but also by inhibitory immune cells such as suppressive dendritic cells and monocyte-derived macrophages (27,28). In fact, IDO expression within the tumor microenvironment and tumor draining lymph nodes correlates with poor cancer prognosis (29)(30)(31)(32). IDO enzymatic activity potentiates tryptophan degradation, causing cell-cycle arrest and induction of anergy in effector T cells.…”
Section: Introductionmentioning
confidence: 99%
“…KN, the first breakdown product of tryptophan mediated by indoleamine-2,3-dioxygenases 1 and 2 (IDO1/2) or tryptophan-2,3-dioxygenase (TDO), activates the aryl hydrocarbon receptor (AhR), a ligand-activated transcription factor, in various tumors (16). KN shows contrasting effects on cell growth depending on cell type; it inhibits growth of lymphoid cell lines (40) while promoting proliferation of non-lymphoid tumor cell lines (22). In the present study, we observed that KN reduced β-catenin expression, which was increased by IDO-1 inhibitor 1-MT.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 4 tryptophan degradation pathways, the KN pathway accounts for ~95% of overall tryptophan degradation (21). IDO-1, which is the first enzyme to metabolize tryptophan along the KN pathway, is expressed in HT-29 cells (22). Thus, we examined whether KN stimulates goblet cell differentiation.…”
Section: Tryptophan and Its Metabolite Kn Promote The Differentiationmentioning
confidence: 99%
“…It has been discovered that kynurenine can enhance polarization of CD4 T cells to a Treg phenotype versus Th17 cells [21,22] . Stimulation of the kynurenine pathway was also shown to create an immune-suppressive milieu in tumor cells through secretion of immunosuppressive tryptophan metabolites that lead to the induction of T cell apoptosis and increased proliferation of immunosuppressive regulatory T cells [23] . Based on these findings, IDO1 is becoming established as a target for drug discovery in cancer [24] .…”
Section: Discussionmentioning
confidence: 99%